Lung torsion after tracheoesophageal fistula repair in an infant - Eun Mi Yang; Eun Song Song; Hae in Jang; In Seok Jeong; Young Youn Choi (Korean Pediatric Society, 2013)
Lung torsion is a very rare event that has been reported in only 9 cases in the pediatric literature but has not yet been reported in Korean infants. We present a case of lung torsion after tracheoesophageal fistula repair in an infant. Bloody secretion from the endotracheal tube and chest radiographs and computed tomographic scan results indicated lung torsion. Emergency exploration indicated 180° torsion of the right upper lobe (RUL) and right middle lobe (RML). After detorsion of both lobes, some improvement in the RUL color was observed, but the color change in the RML could not be determined. Although viability of the RML could not be proven, pexy was performed for both the lobes. Despite reoperation, clinical signs and symptoms did not improve. The bronchoscopy revealed a patent airway in the RUL but not in the RML. Finally, the RML was surgically removed. The patient was discharged on the 42nd day after birth.